Reliability improvement and loss reduction in radial distribution system with network reconfiguration algorithms using loss sensitivity factor - Parasa Sushma Devi; Dasari Ravi Kumar; Kiran Chakravarthula (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Studies on load flow in electrical distribution system have always been an area of interest for research from the previous few years. Various approaches and techniques are brought into light for load flow studies within the system and simulation tools are being used to work out on varied characteristics of system. This study concentrates on these approaches and the improvements made to the already existing techniques considering time and the algorithms complexity. Also, the paper explains the network reconfiguration (NR) techniques considered in reconfiguring radial distribution network (RDN) to reduce power losses in distribution system and delivers an approach to how various network reconfiguration techniques support loss reduction and improvement of reliability in the electrical distribution network.